Age estimation based on the third molar development in a Turkish population: A radiographic study (Annals of Medical Research, 2021)
Aim: The aim of this study was to determine the maturation levels of the third molar teeth of individuals aged between 7 and 25 years, to evaluate the relationship between dental maturation, chronological age and gender, and to test the reliability of this formula by developing regression formulas based on dental maturation data of the third molars for age estimation in a Turkish populatioMaterial and Methods: In this retrospective study, digital panoramic radiographs of a total of 630 patients including 380 females and 250 males, ages 7-25 years were used. The dental maturation of the third molars on the panoramic radiographs was evaluated with the modified Demirjian’s classification system. The descriptive statistics, Cohen’s Kappa, Kolmogorov-Smirnov, Kruskal Wallis, Chi- Square, Mann-Whitney U, Wilcoxon, Spearman Correlation and Linear regression tests were used for statistical analysis.Results: The mean chronological age (CA) was 14.38±2.51 years, with a median age of 14.00 years. Mann-Whitney U test showed that there was no statistically significant difference between the mean CA for females and males (p = 0.968). The mean age difference between the estimated dental age (DA) and CA for females and males was 0.002 and -0.004 years, respectively. This was found not to be statistically significant according to Wilcoxon-signed ranks test (p=0.541).Conclusion: According to the results of this study, the use of third molars as a developmental marker is appropriate. There were no significant differences in third molar development between genders.Keywords: Age estimation; dental age; Demirjian; maturation; third molar.
Keywords: Age estimation; dental age; Demirjian; maturation; third molar.